Catalpol Inhibits Amyloid-β Generation Through Promoting α-Cleavage of APP in Swedish Mutant APP Overexpressed N2a Cells - Wang, Zhuo; Huang, Xueshi; Zhao, Pu; Zhao, Limei; Wang, Zhan-You (Frontiers in Aging Neuroscience, 2018)
Amyloid-β (Aβ) peptides play a crucial role in the pathogenesis of Alzheimer’s disease (AD), due to its neurotoxicity. Thus, blocking Aβ generation and aggregation in the brain has been realized as an efficient way for the prevention of AD. The natural product catalpol, isolated from Rehmannia glutinosa, has shown neuroprotective activities through inhibiting soluble Aβ production, degrading Aβ peptide, and attenuating Aβ toxicity and neuroinflammatory responses. In the present study, we aimed to evaluate whether catalpol reduce Aβ generation associated with regulating amyloid precursor protein (APP) proteolytic processing. By using Swedish mutant APP overexpressed N2a (SweAPP N2a) cells treated with catalpol, we found that catalpol was not able to reduce the expression levels of β-secretase (BACE-1) and γ-secretase (PS1, APH-1, PEN-2 and Nicastrin). By contrast, catalpol had a significant promotion effect on the expression of α-secretase (ADAM10) and its proteolytic products, sAPPα and C83, suggesting that catalpol reduced the production of Aβ might be involved in non-amyloidogenic APP pathway. In addition, we confirmed that the extracellular signal-related kinase/cAMP-response element binding protein (ERK/CREB) signaling pathways were responsible for the up-regulation of ADAM10 in catalpol-treated SweAPP N2a cells. The present data, for the first time, have demonstrated that the effect of catalpol on the inhibiting Aβ generation might be closely related to α-cleavage of APP processing.